Differences in fecal microflora between patients with atopic dermatitis and healthy control subjects - Watanabe, Shinichi; Narisawa, Yutaka; Arase, Seiji; Okamatsu, Hiroshi; Ikenaga, Takeshi; Tajiri, Yoshito; Kumemura, Megumi (Journal of allergy and clinical immunology, 2003)
Background: The prevalence of allergic diseases, such as atopic dermatitis (AD), has been increasing. However, few investigations have been made of the intestinal microflora in Japanese patients with AD. Objective: The purpose of this study was to determine the differences in microflora, fecal serum IgA concentrations, and skin IgA contents between patients with AD and healthy control subjects. Methods: This trial was conducted as a case-control study using 30 minor patients with AD and age- and sex-matched healthy control subjects (n = 68). One week after a questionnaire was administered, fecal specimens and 24-hour skin secretion specimens were collected from all subjects. Fecal microflora, fecal IgA concentrations, and IgA contents on the skin surface were analyzed. Results: The counts of Bifidobacterium (in log10 colony-forming units per gram) were significantly lower in patients with AD than in healthy control subjects (9.75 ± 0.68 vs 10.10 ± 0.50 log10 colony-forming units/g, P < .05). In particular, percentages of Bifidobacterium were significantly lower in patients with severe skin symptoms than in those with mild skin symptoms (40% ± 6% vs 19% ± 6%, P < .05). In addition, the frequency of occurrence of Staphylococcus was significantly higher in patients with AD than in healthy control subjects (83% vs 59%, P < .05). There were no significant differences in fecal IgA content or IgA content on the skin between the 2 groups. Conclusion: Patients with AD had lower counts of Bifidobacterium than healthy control subjects, and the frequency of Staphylococcus was higher in patients with AD than in control subjects. Disorder of the intestinal microflora might play a role in the onset of AD and the aggravation of skin symptoms. (J Allergy Clin Immunol 2003;111:587-91.)